UMA YANOMAMI RADICAL: A GALERIA CLÁUDIA ANDUJAR EM INHOTIM - Rita LAGES RODRIGUES (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
A radical Yanomami: Cláudia Andujar Gallery in Inhotim. Cláudia Andujar Gallery, in Inhotim, was inaugurated in November of 2015. The purpose of this article is to make considerations about the space created to show the artist's photographs, pointing the history of them, especially the images related to the Yanomami Indians. To think about this double of the photographic image, as an index and as an object, is fundamental to use references in the field of photography, anthropology, art history, literature, and gender studies, and with this interdisciplinary reading we seek to understand this specific Andujar work.